Contribution of patient related differences to multidrug resistance in rheumatoid arthritis. Issue 1 (1st January 2003) - Morgan, C; Lunt, M; Brightwell, H; Bradburn, P; Fallow, W; Lay, M; Silman, A; Bruce, I N
Abstract : Background: There is a wide variation in responses to standard disease modifying antirheumatic drug (DMARD) treatment in rheumatoid arthritis (RA). Whether multidrug resistance, failure to respond to several DMARDs, is a specific entity over and above that expected by chance alone is unclear. Objective: To identify patients with RA who demonstrate a multidrug resistant phenotype and to determine what proportion of the variance in drug responses is due to patient related factors. Methods: Patients with RA (1987 American College of Rheumatology criteria) were identified from clinics at Manchester Royal Infirmary and through the Arthritis Research Campaign National RA Repository. The clinic records were reviewed and multidrug resistance was defined as stopping three or more DMARDs owing to lack of efficacy after an adequate trial of the drug. Logistic regression measured by a random effects model was used to determine the relative contribution of the drug and subject related differences to the multidrug resistance. Results: 265 patients (210 (79.3%) female) were studied. The mean (SD) age and disease duration were 52.2 (12.9) and 10.7 (8.8) years, respectively. Patients had a median (range) of 2 (1–8) DMARD courses. Failure of at least one DMARD due to inefficacy occurred in 105 (40%) and 13 (5%) were multidrug resistant. Overall, 35% of the variance in drug responses was due to between-subject differences (p=0.02). Rheumatoid factor (RF) status contributed significantly to this (OR=2.15, 95% confidence interval (95% CI) 1.00 to 4.62) but explained only 3% of the total variance in drug inefficacy. Conclusion: Multidrug resistance occurs in an uncommon (5%) but important subgroup of patients with RA. The between-subject variance is not fully explained by demographics and RF status. Understanding the biological mechanisms that contribute to multidrug resistance may suggest new therapeutic approaches and targets in RA.